Peritonsillar Infiltration of Ropivacaine and Pain Control in Immediate Postoperative Period Following Tonsillectomy Surgery in Adult Patients - Bhandari, Chhanya; Pokharel, Apar; Mayya, Naganavalachil Jayaprakash; Thapa, Ajay Singh (Journal of College of Medical Sciences-Nepal, 2022)
Introduction: To study about the efficacy of Peritonsillar infiltration of Ropivacaine and pain control in immediate postoperative period following tonsillectomy surgery in adult patients. Methods: 80 patients were included in the study of age 18 to 50 years. After informed consent, patients were divided into two groups. In Group R 0.5%Ropivacaine with 1:100000 Adrenaline and in Group C 0.9%normal saline with 1:100000 Adrenaline was injected into the tonsillar fossa following tonsillectomy. Surgery duration, blood loss, time to demand for 1st analgesia, analgesic consumption in 24 hours, and VAS score in 1hr, 2hr, 4hr, 6hr, 12hr, 24hr were noted. Results: We observed significant pain control during first 4 post-operative hours with Value of <0.01, <0.01 and 0.019 respectively in first, second and fourth post-operative score. We also observed significant difference in the time for first analgesia request in two groups with the study group requesting for first analgesic at 518±175 postoperative minutes and control group at 132±47.95 postoperative minutes (P value <0.01). Total analgesia requirement was 61±22.48 in the study group and 102±27.84 in control group (P value < 0.01). Conclusions: It is concluded that intraoperative Peritonsillar infiltration of Ropivacaine causes analgesia in the immediate postoperative hours with the decrease in the requirement of analgesia in the first 24 postoperative hours. It is therefore recommended to use it in adult patient undergoing Tonsillectomy.